Impact of the huge 2011 Tohoku-oki tsunami on the phenotypes and genotypes of Japanese coastal threespine stickleback populations - Manabu Kume (Nature Portfolio, 2018)
Abstract On March 11, 2011, a large earthquake occurred, causing a tsunami which struck the Pacific coast of northeast Japan. We investigated the ecological and genetic effects of the large tsunami on the threespine stickleback (genus Gasterosteus) populations in Otsuchi Town, which was one of the most severely damaged areas after the tsunami. Our environmental surveys showed that spring water may have contributed to the habitat recovery. Morphological analysis of the stickleback before and after the tsunami showed morphological shifts in the gill raker number, which is a foraging trait. Genetic analyses revealed that the allelic richness of one population was maintained after the tsunami, whereas that of another decreased in 2012 and then started to recover in 2013. Additionally, we found that the large tsunami and ground subsidence created new spring water-fed pools with sticklebacks, suggesting that the tsunami brought sticklebacks into these pools. Genetic analysis of this population showed that this population might be derived from hybridization between freshwater Gasterosteus aculeatus and anadromous G. nipponicus. Overall, our data indicate that tsunamis can influence morphologies and genetic structures of freshwater fishes. Furthermore, spring water may play important roles in the maintenance and creation of fish habitats, faced with environmental disturbance.